2010
DOI: 10.1007/s13165-010-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between beneficial invertebrates, field margin vegetation, and thrip damage in organic leek fields in eastern England

Abstract: Beneficial invertebrate numbers in two organic leek fields in eastern England were assessed in relation to four field margin vegetation treatments (clover/grass, regeneration, two flower mixtures) using pitfall and pan traps. Damage caused by onion thrips in one field was also estimated. Clover/grass and regeneration margins generally had more beneficial invertebrates than either flower mixture margins and invertebrate numbers in the fields were least opposite flower mixture margins. Distance from field margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…There is thus a strong need to establish and manage the field margin with plant species that selectively enhance the natural enemies and leave the crop less susceptible to insect pests. However, most of the studies that investigated the effect of well managed field margin vegetation on both beneficial and pest insects reported improved biological control of pest species with few, if any, observations of field margins promoting pest issues (Atakan, 2010; Balzan, Bocci & Moonen, 2016; Balzan & Moonen, 2014; Eyre et al, 2011; Fusser et al, 2016; Holland et al, 2008). For example, aphid densities in broccoli plots surrounded by bare margin were found to be more than four times the aphid densities in plots surrounded by mixed weedy vegetation (Banks, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is thus a strong need to establish and manage the field margin with plant species that selectively enhance the natural enemies and leave the crop less susceptible to insect pests. However, most of the studies that investigated the effect of well managed field margin vegetation on both beneficial and pest insects reported improved biological control of pest species with few, if any, observations of field margins promoting pest issues (Atakan, 2010; Balzan, Bocci & Moonen, 2016; Balzan & Moonen, 2014; Eyre et al, 2011; Fusser et al, 2016; Holland et al, 2008). For example, aphid densities in broccoli plots surrounded by bare margin were found to be more than four times the aphid densities in plots surrounded by mixed weedy vegetation (Banks, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the study by Bianchi & Van Der Werf (2004) who found the availability of non-pest aphids in the non-crop habitats leads to conservation of ladybirds for enhanced biological control. Thrips, aphids and stink bugs damage was reported to be reduced as a result of increased insect natural enemies in different field margin vegetation (Eyre et al, 2011; Alhmedi et al, 2011; Pease & Zalom, 2010). Other insect pests like moth larvae (Balzan & Moonen, 2014) and olive psyllids (Paredes et al, 2013) were also found to be effectively managed through enhanced biological control attributed to the non-crop vegetation diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Intercropping has also been reported to reduce pest incidence on small grain farms in Africa (Pickett, Woodcock, Midega, & Khan, 2014), in citrus orchards intercropped with guava, Psidium guajava L., for psyllid control (Yan, Zenga, & Zhonga, 2015); and where cauliflower, Brassica oleracea var. botrytis L., and leeks, Allium ampeloprasum L., are grown with flowers along the edges to reduce thrips infestations (Eyre, Labanowska-Bury, White, & Leifert, 2011). Some protectant effects of intercropping and vegetational diversification can also be achieved from the increased incidence of natural enemies (Altieri, Schoonhoven, & Doll, 1977;Showler & Reagan, 1991;Showler, 2013) and by trap cropping with other plant species (Vaiyapuri, Amanullah, Rajendran, & Sathyamoorthi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to [16], the population of the arthropods decreases with increasing distance from grassy strips. The effect of distance can be based on the size of the species; the activity density of small carabids decreased, while that of large carabids increased from the field margins [41]. Although the overall results are contradictory, the arthropod diversity decreases from the field edge to the field centre in many investigations.…”
Section: Discussionmentioning
confidence: 99%